EFL teacher cognition in grammar teaching: an investigation in the Saudi Arabian bilingual educational context at university level - Ahmad, Iftikhar (2019)
This study is an investigation of EFL teacher cognition in teaching grammar to university students in the Saudi Arabian bilingual educational context. As reflected in literature review, much research has been conducted in the domain of EFL teacher cognition in monolingual context but little in bilingual context. Working on this under-researched area, the present study seeks to understand EFL teachers’ beliefs and practices in grammar teaching and the role of their bilinguality in grammar teaching. The study employs a mixed methods approach involving belief questionnaire, structured classroom observations and semi-structured interviews. The sample of the study comprises 132 native Arabic speaking and non-Arab EFL teachers for questionnaire, based on stratified random sampling, and eight teachers each for structured classroom observations and semi-structured interviews, based on purposeful sampling. The sample also consists of four students and four administrators, who were interviewed to triangulate teachers’ interviews, and confirm teachers’ identification of the contextual factors influencing their cognition in teaching grammar to university students in Saudi Arabia. The results of the study reveal that teachers’ beliefs stem from idealization of the grammar teaching process resulting into several paradoxes. The paradoxes reflect inconsistencies between their own deep seated beliefs and the beliefs they perform to project, to be more in line with the institutional policies. In the same way, several differences have been explored between beliefs and practices of grammar teachers. Teachers project themselves as innovative practitioners and claim to believe in teaching grammar through student-centered methods following communicative approach; in reality their practices are teacher-centered and traditional, with little opportunity for students to use grammar in context. The study finds out that these differences are due to the contextual factors: social, institutional, and demotivated students. The results also reveal that less experienced teachers do not tolerate students’ errors and are rigid in their grammar teaching approach. This indicates their lack of understanding of the dynamics of the teaching context. The findings indicate that non-Arab teachers believe in limited and judicious use of Arabic, while Arab teachers believe in frequent use of Arabic in grammar teaching, rather than using it as a pedagogical tool and scaffolding. The study is significant for its practical implications for EFL Arab and non-Arab teachers, male and female teachers, and experienced and less-experienced teachers in teaching grammar to university students. The study has suggested procedures for the teachers, policy makers and teacher trainers to improve grammar teaching in the bilingual EFL context in Saudi Arabia. The study has also suggested recommendations for further research in the same area.